Imaging in Splenic Pathologies: A Pictorial Review - Sandhu, Gurpreet Singh; Singh, Lokesh; Debi, Uma; Rana, Pratyaksha; Bhatia, Vikas; S, Sandhu M (Archives of Clinical and Medical Case Reports, 2020)
Splenic lesions are uncommon and encountered less commonly than pathologies of other visceral organs. However radiological evaluation and diagnosis of these lesions using ultrasound, Computed tomography and Magnetic resonance imaging has good specificity in differentiating congenital, benign and malignant lesions. The purpose of this pictorial essay is to offer a review of the common and uncommon splenic pathologies and illustrating the typical imaging features of these lesions.